On the seismic performance of straight integral abutment bridges: From advanced numerical modelling to a practice‐oriented analysis method. (5th November 2022) - Marchi, Andrea; Gallese, Domenico; Gorini, Davide Noè; Franchin, Paolo; Callisto, Luigi
Abstract: The seismic performance of integral abutment bridges (IABs) is affected by the interaction with the surrounding soil, and specifically by the development of interaction forces in the embankment‐abutment and soil‐piles systems. In principle, these effects could be evaluated by means of highly demanding numerical computations that, however, can be carried out only for detailed studies of specific cases. By contrast, a low‐demanding analysis method is needed for a design‐oriented assessment of the longitudinal seismic performance of IABs. To this purpose, the present paper describes a design technique in which the frequency‐ and amplitude‐dependency of the soil‐structure interaction is modelled in a simplified manner. Specifically, the method consists of a time‐domain analysis of a simplified soil‐bridge model, in which soil‐structure interaction is simulated by means of distributed nonlinear springs connecting a free‐field ground response analysis model to the structural system. The results of this simplified method are validated against the results of advanced numerical analyses, considering different seismic scenarios. In its present state of development, the proposed simplified nonlinear model can be used for an efficient evaluation of the longitudinal response of straight IABs and can constitute a starting point for a prospective generalisation to three‐dimensional response.